2002
DOI: 10.1098/rsta.2002.0995
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the formation of cosmic structure

Abstract: A timely combination of new theoretical ideas and observational discoveries has brought about significant advances in our understanding of cosmic evolution. Computer simulations have played a key role in these developments by providing the means to interpret astronomical data in the context of physical and cosmological theory. In the current paradigm, our Universe has a flat geometry, is undergoing accelerated expansion and is gravitationaly dominated by elementary particles that make up cold dark matter. With… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…More extensive reviews of the cold dark matter cosmological model can be found in, for example, Narlikar and Padmanabhan (2001), Frenk (2002) and Bertone et al (2005).…”
Section: Background Materialsmentioning
confidence: 99%
“…More extensive reviews of the cold dark matter cosmological model can be found in, for example, Narlikar and Padmanabhan (2001), Frenk (2002) and Bertone et al (2005).…”
Section: Background Materialsmentioning
confidence: 99%
“…The properties of dark matter haloes in the context of the LCDM paradigm have been studied in detail using numerical simulations over the past couple of decades with increasing resolution (e.g. Davis et al 1985; Efstathiou et al 1988; Frenk et al 1988; Katz, Hernquist & Weinberg 1999; Kauffmann et al 1999; Bullock et al 2001b; Frenk 2002; Springel et al 2005). This approach has been very fruitful in providing us with a detailed picture of the assembly and growth of structure in the Universe.…”
Section: Introductionmentioning
confidence: 99%
“…Since cdm is supposed to be electrically neutral, it is not linked by Coulomb interactions to the baryon-photon fluid. Therefore, researchers [8,9] in the field of structure formation have assumed in their simulations that cdm would have already clustered before decoupling and thus would have formed seeds for baryon contraction after decoupling. If this would be true, then the slow growth (2) would be sufficient to explain structure in the universe.…”
Section: A Former Results: Standard Perturbation Theorymentioning
confidence: 99%